(untitled) (Contemporary Education and Teaching Research, 2025)
This study examines the collaborative development of traditional culture education in the Guangdong–Hong Kong–Macao Greater Bay Area (GBA). Drawing on Triadic Reciprocal Determinism (TRD) and the Cultural Knowings Framework (CKF), it employs a descriptive comparative analysis to systematically review policy documents, curriculum standards, teaching guidelines, and educational reports released between 2016 and 2024 by education authorities in Guangdong, Hong Kong, and Macao. The findings reveal marked regional distinctions in structural orientation and pedagogical focus. The nine mainland GBA cities emphasize systematic curriculum alignment and school-based cultural experiences, while Hong Kong and Macao highlight multicultural integration, project-based learning, and technology-enabled engagement. Despite these distinctive strengths, all three regions face persistent structural “embedding” challenges and a lack of robust cross-regional coordination mechanisms. To address these challenges, the study proposes a coordination framework centered on person–behavior–environment interactions, articulating a four-stage progression—cognition, participation, reflection, and identification—to integrate regional resources, reinforce shared cultural foundations, and promote sustainable collaboration while respecting local diversity. The study advances theoretical integration, model construction, and practical implications by linking the TRD and the CKF for the first time to develop an operational model for regional cultural collaboration. This framework offers both analytical and practical value, providing new pathways for curriculum design, policy coordination, and cultural governance across the GBA.